Preparation method of biological carrier suitable for growth of nitrosobacteria and anaerobic ammonium oxidation bacteria
By designing carriers with pore size differences in sewage treatment and adjusting the dissolving oxygen distribution, the carrier surface suitable for the growth of nitroscopic bacteria and anaerobic ammonia oxidizing bacteria is solved, and the coordinated growth of bacteria and the improvement of sewage treatment efficiency is achieved.
Patent Information
- Application Number
- CN202510071641.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-16
AI Technical Summary
In the existing wastewater treatment technology, nitroscopic bacteria and anaerobic ammonia oxidizing bacteria need to control the distribution of dissolved oxygen when coexisting, resulting in slow growth rate of biofilm and low adhesion efficiency of carriers to autotrophic bacteria.
By controlling the pressure to synthesize a carrier with pore size difference and adjusting the dissolved oxygen distribution in different regions in the reactor, a carrier surface suitable for AOB and AnAOB growth is constructed to promote the coordinated growth of the two types of bacteria. Specific methods include preparing amino-rich cationic gels and large pore carriers, and enhancing the hydrophilicity and positive potential of the carrier surface through aeration and crosslinking modification techniques.
The biofilm adhesion speed and adhesion strength of nitroscopic bacteria and anaerobic ammonia oxidizing bacteria have been improved, and their synergistic growth has been promoted, which has solved the limitations of the carrier on the growth of autotrophic bacteria and improved the sewage treatment efficiency.
Smart Images

Figure CN119797579A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of sewage treatment, and in particular relates to a method for preparing a biological carrier suitable for the growth of nitrite bacteria and anaerobic ammonia oxidizing bacteria. Background Art
[0002] The partial nitration-anammox denitrification process has the advantage of energy saving. Nitrosifying bacteria (AOB) oxidize ammonia nitrogen to nitrite nitrogen, which requires an aerobic environment, while anaerobic ammonia oxidizing bacteria (AnAOB) convert ammonia nitrogen and the generated nitrite nitrogen into nitrogen gas to achieve the purpose of wastewater denitrification, but it needs to be carried out in a strictly anaerobic environment. Since AOB is an aerobic bacterium and AnAOB is a strictly anaerobic bacterium, when the two coexist in the same reactor, it is necessary to control the content of dissolved oxygen to ensure the growth of both. Therefore, the control of the local environment dissolved oxygen distribution is the key to the synergistic growth of the two types of bacteria, that is, the presence of aerobic and anaerobic areas at the same time. In addition, AOB and AnAOB are both autotrophic bacteria with slow growth. By adding carriers, the concentration of AOB and AnAOB bacteria in the reactor can be increased, but at present, the carrier generally has the problem of slow biofilm growth rate for autotrophic bacteria. By constructing carrier surfaces suitable for the growth and attachment of AOB and AnAOB bacteria, the shortcomings of the current synergistic growth and the existence of carriers can be overcome.
[0003] The growth of microbial biofilm on the carrier surface is related to the functional groups, potential and porosity of the carrier surface. Introducing hydrophilic groups (such as carboxyl, amino, hydroxyl, sulfonic acid, etc.) on the carrier surface can enhance the hydrophilicity of the carrier surface, and the polar groups on the carrier surface have stronger hydrogen bonding with substances such as proteins, polysaccharides and DNA on the microbial surface, which is conducive to enhancing the attachment speed and strength of microorganisms. In addition, since most carrier surfaces are negatively charged, and the surface of microorganisms in water also has the property of surface negative charge, this causes electrostatic repulsion between microorganisms and the carrier surface, resulting in low adhesion of microorganisms on its surface, easy detachment of biofilms, and long system startup time. Studies have found that the biofilm on the surface of carriers with smaller pore sizes has high stability, but the oxygen penetration efficiency is low when the biofilm is formed; while the biofilm on the surface of carriers with large pore sizes has high diversity but poor stability, and good oxygen penetration ability. Summary of the invention
[0004] In view of the above problems, the present invention provides a method for preparing a biological carrier suitable for the growth of nitrite bacteria and anaerobic ammonia oxidizing bacteria. The present invention synthesizes a carrier with different pore sizes by controlling the pressure, controls the distribution of dissolved oxygen in different regions of the carrier in the reactor, and promotes the coordinated growth of AOB and AnAOB biofilms in different regions of the carrier by constructing a carrier surface suitable for the growth of AOB and AnAOB.
[0005] The method for preparing a biological carrier suitable for the growth of nitrite bacteria and anaerobic ammonia oxidizing bacteria of the present invention comprises the following steps:
[0006] Step 1: Preparation of amino-rich cationic gel
[0007] The magnesium oxide particles were put into a mortar for grinding, and the particle size determined by passing through a 150-mesh sieve after grinding was about 100 μm. The powdered chitosan was placed in a 10% acetic acid solution and fully dissolved at 80°C to prepare a chitosan solution; the magnesium oxide powder was added to the chitosan solution and stirred evenly, and then a 2% by mass glutaraldehyde solution was added for cross-linking modification to obtain a cationic gel rich in amino groups.
[0008] In step 1, the mass fraction of chitosan in the chitosan solution is 2% to 4%. The mass ratio of the chitosan solution to the glutaraldehyde solution is 250:1.
[0009] In step 1, the content of magnesium oxide in the amino-rich cationic gel is 3%.
[0010] Step 2: Preparation of a macroporous support that facilitates gas exchange
[0011] A blowing agent, a stabilizer, a polyether polyol, triethanolamine and dimethylolbutyric acid are added into a reactor in a certain proportion, isocyanate is slowly added thereto, and the mixture is stirred at a speed of 600-900 rpm for 2-4 hours under the conditions of a vacuum degree of 0.10-0.12 MPa and a temperature of 25±2°C, and ripened to obtain a polyurethane soft foam; the obtained polyurethane soft foam is placed in a sealed reticulated device, filled with nitrogen, and a polyurethane film in the pores is dissolved using an N,N-dimethylformamide solution to ensure that a pore size of 2 mm-4 mm is formed on the surface of the carrier.
[0012] In step 2, the components are composed of 4 to 8 parts of foaming agent, 2 to 3 parts of stabilizer, 100 parts of polyether polyol, 6 parts of triethanolamine, 3 parts of dimethylolbutyric acid, and 1.14 parts of isocyanate in terms of mass fraction.
[0013] The foaming agent is a mixture of triethylamine and dichloromethane, and the mass ratio of the two is 1:1; the stabilizer is silicone oil; the polyether polyol is selected from one or more of polyether 330, polyether 330N, polyether 320, polyether 230, polyether 220, etc. The isocyanate is selected from one or more of toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, and naphthalene-1,5-diisocyanate. When the foam is uniformly matured under low temperature conditions, the temperature is controlled between 25±2°C.
[0014] In step 2, the nitrogen inflation pressure is 0.10 MPa~0.11 MPa.
[0015] Step 3: Preparation of nitrosated carrier with positive potential and hydrophilic groups on the surface
[0016] Fill the amino-rich cationic gel prepared in step 1 with oxygen to generate bubbles inside the gel. When uniform and fine bubbles are formed inside the gel, immerse the large-pore carrier prepared in step 2 in the gel for 5 minutes. Take out the carrier and put it in a 60°C drying oven for drying for 1 hour before taking it out. Repeat the above steps 2 to 3 times to ensure that the gel is fully and evenly coated on the surface of the carrier.
[0017] Step 4: Preparation of Amino-enriched Iron-containing Gel
[0018] The iron oxide was put into a mortar for grinding, and after grinding, the particle size of the two was determined to be about 100 μm by passing through a 150-mesh sieve. Powdered chitosan was placed in a 10% acetic acid solution and fully dissolved at 80°C to prepare a chitosan solution; iron oxide powder was added to the chitosan solution, and then a 2% by mass glutaraldehyde solution was added for cross-linking modification to obtain a cationic gel rich in amino groups.
[0019] In step 4, the mass fraction of chitosan in the chitosan solution is 2% to 4%. The mass ratio of the chitosan solution to the glutaraldehyde solution is 250:1.
[0020] The mass fraction of iron oxide in the amino-rich cationic gel prepared in step 4 is 5%.
[0021] Step 5: Preparation of small pore size carriers for controlling dissolved oxygen permeation
[0022] Add the blowing agent, polyether polyol and catalyst into the carrier mold, and gradually add the aromatic diisocyanate during stirring. At this time, uniform and fine bubbles will gradually form inside the system. Place the obtained polyurethane soft foam in a sealed reticulated device, fill it with nitrogen, and use N,N-dimethylformamide solution to dissolve the polyurethane film in the pores to ensure that a pore size of 0.3mm~0.4mm is formed on the carrier surface.
[0023] In step 5, the components are composed of 4 to 8 parts of blowing agent, 70 to 80 parts of polyether polyol, 0.5 to 1.5 parts of catalyst, and 7 to 8 parts of aromatic diisocyanate in parts by mass.
[0024] The foaming agent is a mixture of triethylamine and dichloromethane, and the mass ratio of the two is 1:1. The polyether polyol is selected from one or more of polyether 330, polyether 330N, polyether 320, polyether 230, polyether 220, etc. The catalyst is dibutyltin dilaurate. The aromatic diisocyanate is selected from one or more of toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, and naphthalene-1,5-diisocyanate. When the foam is uniformly matured under low temperature conditions, the temperature is controlled between 30°C and 40°C.
[0025] In step 5, after filling with nitrogen, the pressure is controlled at 0.05 MPa~0.08 MPa to control the size of the foam.
[0026] Step 6: Preparation of anaerobic ammonium oxidation carrier with iron ions and hydrophilic groups on the surface
[0027] Fill the gel prepared in step 4 with hydrogen to generate bubbles inside the gel. When uniform and fine bubbles are formed inside the gel, immerse the small-pore carrier prepared in step 5 in the gel for 5 minutes. Take out the carrier and put it in a 60°C drying oven for drying for 1 hour before taking it out. Repeat the above steps 2 to 3 times to ensure that the hydrogel is fully and evenly coated on the surface of the carrier.
[0028] Step 7: Combination of nitrite carrier and anaerobic ammonium oxidizing bacteria carrier
[0029] Using polyurethane glue as an adhesive (diluted with acetone in an amount of one third to one half of its volume before use), the nitrite carrier prepared in step 3 is combined with the anaerobic ammonium oxidation carrier prepared in step 6, wherein the nitrite carrier prepared in step 3 is used as the top and bottom layers (AOB adsorption carrier), and the anaerobic ammonium oxidation carrier prepared in step 6 is used as the middle layer (AnAOB adsorption carrier), to form a sandwich structure.
[0030] During the specific operation, evenly coat one side of the AOB adsorption carrier with the diluted polyurethane glue, then spread it flat on the grid and let it stand for 5 minutes to ensure that the polyurethane glue no longer drips. After the polyurethane glue is slightly sticky, place the AOB adsorption carrier close to the surface of the AnAOB adsorption carrier to ensure that the AnAOB carrier is completely wrapped. Place the entire carrier in an oven at 60°C for drying. After drying, take out the carrier and place it in ultrapure water, and use ultrasonic equipment to clean it for 30 minutes to remove impurities and uncured adhesive on the surface.
[0031] In step 7, the polyurethane adhesive is obtained by self-production. The specific steps are: 1 part of toluene diisocyanate is dissolved in 50 parts of N,N-dimethylformamide (DMF) and prepolymerized for 5 minutes. Then, 1 part of polyethylene glycol is added to the solution. Then, the mixture is fully mixed and stirred at room temperature, and the whole reaction process lasts for 2 hours.
[0032] The bionic carrier prepared by the invention is used in the PN / A integrated process and can promote the rapid enrichment of microorganisms.
[0033] The present invention has the following advantages and positive effects:
[0034] (1) The present invention utilizes pressure differences to construct polyurethane carriers with different pore sizes, and controls the distribution of dissolved oxygen in the reactor by adjusting the pore size of the polyurethane carrier, thereby creating conditions for the co-enrichment of nitrite-reducing bacteria and anaerobic ammonium oxidation.
[0035] (2) The present invention uses polyurethane material as the supporting matrix of the biofilm and uses chitosan adsorption gel as the hydrophilic modified substance. Since the surface of chitosan contains abundant amino groups and hydroxyl groups, the introduction of chitosan enhances the hydrophilicity of the carrier surface, which is conducive to accelerating the attachment of the biofilm. In addition, the preparation of chitosan gel is simple, which is conducive to industrial production.
[0036] (3) When the chitosan gel is loaded onto the surface of the carrier, the chitosan gel is aerated to generate uniform bubbles, which helps to increase the surface area of the carrier. When oxygen aeration is used, it helps to maintain the oxidized groups on the surface of the chitosan, thereby promoting the attachment of microorganisms to the carrier.
[0037] (4) The present invention uses magnesium oxide and iron oxide to enhance the positive potential of the carrier surface. Magnesium oxide has a high isoelectric point and carries more positive charges on the surface. The hydrogel loaded with magnesium oxide carries positive charges. When the hydrogel is added to the carrier surface, the positive potential of the carrier surface can be effectively increased. Iron oxide powder can accelerate the aggregation of anaerobic ammonia-oxidizing bacteria due to the iron-loving nature of anaerobic ammonia-oxidizing bacteria and the positive potential on its surface.
[0038] (5) The present invention adopts the gluing method to splice two carriers, which is simple to operate and easy to produce.
[0039] (6) The carrier prepared by the present invention has the characteristics of high porosity, low relative density, high mechanical strength, corrosion resistance and aging resistance, and can be applied to various reactors such as UASB and CSTR. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The present invention is a flow chart for preparing a biological carrier suitable for the growth of nitrite-oxidizing bacteria and anaerobic ammonia-oxidizing bacteria.
[0041] Figure 2 It is a structural schematic diagram and working principle of the biological carrier suitable for the growth of nitrite bacteria and anaerobic ammonia oxidizing bacteria of the present invention.
[0042] Figure 3 It is a schematic diagram of the structure of the biological carrier suitable for the growth of nitrite bacteria and anaerobic ammonia oxidizing bacteria of the present invention.
[0043] Figure 4 It is the water contact angle of the surface of amino gel with different contents in the present invention.
[0044] Figure 5 It is the adsorption effect of the nitrite carrier with positive potential and hydrophilic group characteristics on the surface of the present invention on the activated sludge.
[0045] Figure 6 The invention relates to the adsorption effect of the anaerobic ammonia oxidation carrier having iron ions and hydrophilic groups on the surface on the activated sludge.
[0046] Figure 7 The invention discloses an adsorption effect of the biological carrier suitable for the growth of nitrite bacteria and anaerobic ammonia oxidizing bacteria on activated sludge. DETAILED DESCRIPTION
[0047] The present invention will be further described below in conjunction with the accompanying drawings and specific implementation methods.
[0048] The present invention provides a method for preparing a biological carrier suitable for the growth of nitrite bacteria and anaerobic ammonia oxidizing bacteria, which is specifically as follows:
[0049] (1) Preparation of cationic gel rich in amino groups. Magnesium oxide particles were ground into a mortar and then passed through a 150-mesh sieve to determine that the particle size of the two particles was about 100 μm. Powdered chitosan was placed in a 10% acetic acid solution and fully dissolved at 80°C to prepare a chitosan solution in which the mass fraction of chitosan was 2% to 4%. 3% magnesium oxide powder was added to the gel and stirred evenly. A 2% mass fraction glutaraldehyde solution was added to the chitosan gel for cross-linking modification to obtain a cationic gel rich in amino groups. The mass ratio of the chitosan solution to the glutaraldehyde solution was 250:1 and stirred for 1-2 hours.
[0050] (2) Preparation of large-pore carriers that are conducive to gas exchange. Add a certain proportion of foaming agent, stabilizer, polyol, triethanolamine and dimethylolbutyric acid into the reactor, slowly add isocyanate into it and stir at a speed of 600-900 rpm for 2-4 hours under the conditions of vacuum degree of 0.10-0.12 MPa and temperature of 25±2°C, and ripen to obtain polyurethane soft foam. Among them, 4-8 parts of foaming agent, 2-3 parts of stabilizer, 100 parts of polyether polyol, 6 parts of triethanolamine, 3 parts of dimethylolbutyric acid, and 1.14 parts of isocyanate are placed in a sealed mesh device and filled with nitrogen. The inflation pressure is 0.10 MPa-0.11 MPa. The inflated polyurethane carrier is dissolved in the polyurethane film in the pores using N,N-dimethylformamide solution to ensure that the carrier surface forms a pore size of about 2mm-4mm. The foaming agent is a mixture of triethylamine and dichloromethane, the mass ratio of the two is 1:1, the stabilizer is silicone oil, and the polyether polyol is selected from one or more of polyether 330, polyether 330N, polyether 320, polyether 230, polyether 220, etc. The catalyst is dibutyltin dilaurate. The isocyanate is selected from one or more of toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, and naphthalene-1,5-diisocyanate.
[0051] (3) Preparation of a nitrosated carrier with positive potential and hydrophilic group characteristics on the surface. Oxygen is injected into the gel prepared in (1) to generate bubbles inside the gel. When uniform and fine bubbles are formed inside the gel, the large-pore carrier prepared in step 2 is immersed in the gel for 5 minutes. The carrier is taken out and placed in a 60°C drying oven for drying for 1 hour before being taken out. Repeat the above steps 2 to 3 times to ensure that the hydrogel is fully and evenly coated on the carrier surface.
[0052] (4) Preparation of iron-containing gel rich in amino groups. The iron oxide was ground into a mortar and then passed through a 150-mesh sieve to determine that the particle size of the two was about 100 μm. Powdered chitosan was placed in a 10% acetic acid solution and fully dissolved at 80°C to prepare a chitosan solution in which the mass fraction of chitosan was 2% to 4%. After adding iron oxide powder to the gel, a 2% glutaraldehyde solution was added to the chitosan gel for cross-linking modification to obtain an amino-rich cationic gel. The mass ratio of the chitosan solution to the glutaraldehyde solution was 250:1, and magnetic stirring was performed for 1-2 hours. The mass fraction of the iron oxide powder was 5%.
[0053] (5) Preparation of small-pore carriers for controlling dissolved oxygen penetration. Add a foaming agent, a polyether polyol and a catalyst to the carrier mold according to their mass. The mass fractions of each component are 4-8 parts of a foaming agent, 70-80 parts of a polyether polyol and 0.5-1.5 parts of a catalyst. During the stirring process, gradually add aromatic diisocyanates, wherein the isocyanate is 7-8 parts. At this time, uniform and fine bubbles will gradually form inside the system. Nitrogen is filled into the polyurethane soft foam placed in a sealed mesh device, and the pressure is controlled at 0.05 MPa-0.08 MPa to control the foam size. The inflated polyurethane carrier is dissolved in an N,N-dimethylformamide solution in the pores of the polyurethane carrier to ensure that a pore size of about 0.3 mm to 0.4 mm is formed on the surface of the carrier. The foaming agent is a mixture of triethylamine and dichloromethane, and the mass ratio of the two is 1:1. The polyether polyol is selected from one or more of polyether 330, polyether 330N, polyether 320, polyether 230, polyether 220, etc. The catalyst is dibutyltin dilaurate. The isocyanate is selected from one or more of toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, and naphthalene-1,5-diisocyanate. When the foam is uniformly matured under low temperature conditions, the temperature is controlled between 30°C and 40°C.
[0054] (6) Preparation of small-pore anaerobic ammonium oxidation carriers rich in amino groups and iron ions. Hydrogen is injected into the gel prepared in (4) to generate bubbles inside the gel. When uniform and fine bubbles are formed inside the gel, the large-pore carrier prepared in step 2 is immersed in the gel for 5 minutes. The carrier is taken out and placed in a 60°C drying oven for 1 hour before being taken out. Repeat the above steps 2 to 3 times to ensure that the hydrogel is fully and evenly coated on the surface of the carrier.
[0055] (7) Combination of nitrite carrier and anaerobic ammonia oxidizing bacteria carrier. The carriers prepared in (3) and (6) were combined by gluing, wherein the large-pore carrier was used as the outer layer and the small-pore carrier was used as the inner layer. The adhesive was polyurethane glue, and the specific preparation method was as follows: 1 part of toluene diisocyanate was dissolved in 50 parts of N,N-dimethylformamide (DMF) and prepolymerized for 5 minutes. Then 1 part of polyethylene glycol was added to the solution. Then, the mixture was mixed and stirred at room temperature, and the whole reaction process lasted for 2 hours. Acetone was added to the polyurethane glue in an amount of one-third of its volume to dilute it. One side of the AOB adsorption carrier was evenly coated with the diluted polyurethane glue, and then it was spread flat on the grid and left to stand for 5 minutes to ensure that the polyurethane glue no longer dripped. After the polyurethane glue became slightly sticky, the AOB adsorption carrier was pressed against the surface of the AnAOB adsorption carrier to ensure that the AnAOB carrier was completely wrapped. The entire carrier was placed in an oven at 60°C for drying. After drying, the carrier was taken out and placed in ultrapure water and cleaned using an ultrasonic device for 30 minutes to remove surface impurities and uncured adhesive.
[0056] Example 1: Study on the Optimal Addition Amount of Chitosan in Amino-Rich Gel
[0057] Chitosan with 1%, 2%, 3%, and 4% chitosan was placed in 10% acetic acid solution, fully dissolved at 80°C, and prepared into chitosan solution. A 2% glutaraldehyde solution was added to the chitosan gel for cross-linking modification, wherein the mass ratio of chitosan solution to glutaraldehyde solution was 250:1, and stirred for 1-2 hours. The gel was poured on a plate to form a thin film and the water contact angle on its surface was measured. It was finally found that the water contact angle increased with the increase of chitosan content, which was 76.8°, 63.1°, 56°, and 42.7°, respectively. In theory, the higher the chitosan content, the better its hydrophilicity, but higher hydrophilicity will also inhibit the attachment and growth of microorganisms, so the chitosan content was set at 3%.
[0058] Example 2: Preparation of nitrosated carriers with positive potential and hydrophilic groups on the surface and study of their adsorption on microorganisms
[0059] 1. Put the magnesium oxide particles into a mortar and grind them. After grinding, pass through a 150-mesh sieve to determine that the particle size of the two is about 100 μm. Place the powdered chitosan in a 10% acetic acid solution and fully dissolve it at 80°C to prepare a chitosan solution in which the mass fraction of chitosan is 3%. Add 3% magnesium oxide powder to the gel and stir evenly. Add a 2% mass fraction glutaraldehyde solution to the chitosan gel for cross-linking modification to obtain an amino-rich cationic gel. The mass ratio of the chitosan solution to the glutaraldehyde solution is 250:1 and stir for 1-2 hours.
[0060] 2. Add the blowing agent, stabilizer, polyol, triethanolamine and dimethylolbutyric acid into the reactor in a certain proportion, add isocyanate thereto, stir at a speed of 600-900rpm for 2-4h under the conditions of vacuum degree of 0.10-0.12MPa and temperature of 25±2℃, and ripen to obtain polyurethane soft foam. Among them, there are 6 parts of blowing agent, 3 parts of stabilizer, 100 parts of polyether polyol, 6 parts of triethanolamine, 3 parts of dimethylolbutyric acid, and 1.14 parts of isocyanate. The polyurethane soft foam is placed in a sealed mesh device and filled with nitrogen at a pressure of 0.10 MPa-0.11MPa. The inflated polyurethane carrier is dissolved with N,N-dimethylformamide solution in the pores of the polyurethane film to ensure that the carrier surface forms a pore size of about 2mm-4mm.
[0061] 3. Fill the prepared gel with oxygen to generate bubbles inside the gel. When uniform and fine bubbles are formed inside the gel, immerse the prepared carrier in the gel for 5 minutes, take out the carrier and put it into a 60℃ drying oven for drying for 1 hour before taking it out. Repeat the above steps 2-3 times to ensure that the hydrogel is fully and evenly coated on the surface of the carrier.
[0062] (1) Preparation without adding cationic gel carrier
[0063] Add a blowing agent, a stabilizer, a polyol, triethanolamine and dimethylolbutyric acid to a reactor in a certain proportion, add isocyanate thereto, stir at a speed of 600-900rpm for 2-4h under the conditions of vacuum degree of 0.10-0.12MPa and temperature of 25±2℃, and ripen to obtain a polyurethane soft foam. Among them, there are 6 parts of blowing agent, 3 parts of stabilizer, 100 parts of polyether polyol, 6 parts of triethanolamine, 3 parts of dimethylolbutyric acid, and 1.14 parts of isocyanate. The polyurethane soft foam is placed in a sealed mesh device and filled with nitrogen, and the inflation pressure is 0.10 MPa-0.11MPa. The inflated polyurethane carrier is dissolved in the polyurethane film in the pores using N,N-dimethylformamide solution to ensure that the carrier surface forms a pore size of about 2mm-4mm. Powdered chitosan is placed in a 10% acetic acid solution, fully dissolved at 80℃, and prepared into a chitosan solution, in which the mass fraction of chitosan is 3%. Add 2% glutaraldehyde solution to chitosan gel for cross-linking modification to obtain amino-rich cationic gel. The mass ratio of chitosan solution to glutaraldehyde solution is 250:1. Stir for 1-2 hours. Fill the prepared gel with oxygen to generate bubbles inside the gel. When uniform and fine bubbles are formed inside the gel, immerse the prepared large-pore carrier in the gel for 5 minutes. Take out the carrier and put it into a 60°C drying oven for drying for 1 hour before taking it out. Repeat the above steps 2-3 times to ensure that the hydrogel is fully and evenly coated on the carrier surface.
[0064] (2) Preparation of the control group
[0065] Add a blowing agent, a stabilizer, a polyol, triethanolamine and dimethylolbutyric acid to a reactor in a certain proportion, add isocyanate thereto, stir at a speed of 600-900rpm for 2-4 hours under the conditions of a vacuum degree of 0.10-0.12MPa and a temperature of 25±2°C, and ripen to obtain a polyurethane soft foam. Among them, there are 6 parts of blowing agent, 3 parts of stabilizer, 100 parts of polyether polyol, 6 parts of triethanolamine, 3 parts of dimethylolbutyric acid, and 1.14 parts of isocyanate. The polyurethane soft foam is placed in a sealed mesh device and filled with nitrogen at a pressure of 0.10 MPa-0.11MPa. The inflated polyurethane carrier is dissolved in the polyurethane film in the pores using N,N-dimethylformamide solution to ensure that a pore size of about 2mm-4mm is formed on the carrier surface.
[0066] Prepare three 250mL conical flasks, add activated sludge of the same concentration and three groups of different carriers, 10 each. The carrier without gel was used as the control group, the carrier with only gel was used as experimental group 1, and the carrier with amino-rich cationic gel was used as experimental group 2. At a temperature of 25±2℃, the beaker was stirred at a speed of about 300rpm with a shaker, and the carrier in the beaker was taken out every 3 minutes, and the surface water was drained and weighed to detect the change of the activated sludge mass adsorbed by the carrier over time.
[0067] As shown in the figure, the carrier with amino-rich cationic gel has the best adsorption effect on activated sludge. It was also found that the adsorption effect on activated sludge was significantly improved after adding amino-rich gel compared with the carrier without any substance added. The adsorption amount of activated sludge on the surface of the carrier without any substance added reached 0.8 g / (g carrier), while the adsorption amount of activated sludge by adding amino-rich gel carrier reached 2.2 g / (g carrier), and the adsorption amount of activated sludge by adding amino-rich cationic gel carrier reached 2.35 g / (g carrier). Compared with the large-pore carrier without the addition of cationic gel, it increased by 1.55 g / (g carrier).
[0068] Example 3: Preparation of small-pore anaerobic ammonium oxidation carrier rich in amino groups and iron ions
[0069] 1. Put the iron oxide into a mortar and grind it. After grinding, pass it through a 150-mesh sieve to determine that the particle size of the two is about 100 μm. Place the powdered chitosan in a 10% acetic acid solution and fully dissolve it at 80°C to prepare a chitosan solution in which the mass fraction of chitosan is 3%; add the iron oxide powder to the gel and then add a 2% glutaraldehyde solution to the chitosan gel for cross-linking modification to obtain an amino-rich cationic gel. The mass ratio of the chitosan solution to the glutaraldehyde solution is 250:1, and magnetic stirring is performed for 1-2 hours. The mass fraction of the iron oxide powder is 5%.
[0070] 2. Add a foaming agent, polyether polyol and catalyst to the mold according to mass. The mass fraction of each component is 6 parts of foaming agent, 70 parts of polyether polyol and 1.5 parts of catalyst. During the stirring process, aromatic diisocyanate is gradually added, wherein 7 parts of isocyanate. At this time, uniform and fine bubbles will gradually form inside the system. Nitrogen is filled into the polyurethane soft foam placed in a sealed mesh device, and the pressure is controlled at 0.05 MPa~0.08 MPa to control the foam size. The inflated polyurethane carrier is dissolved in the polyurethane film in the pores using N,N-dimethylformamide solution to ensure that the carrier surface forms a pore size of about 0.3mm~0.4mm. The foaming agent is a mixture of triethylamine and dichloromethane, and the mass ratio of the two is 1:1. The polyether polyol is selected from one or more of polyether 330, polyether 330N, polyether 320, polyether 230, polyether 220, etc. The catalyst is dibutyltin dilaurate. The isocyanate is selected from one or more of toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, and naphthalene-1,5-diisocyanate. When the foam is uniformly matured under low temperature conditions, the temperature is controlled between 30°C and 40°C.
[0071] 3. Fill the prepared gel with hydrogen to generate bubbles inside the gel. When uniform and fine bubbles are formed inside the gel, immerse the large-pore carrier in the gel for 5 minutes, take out the carrier and put it into a 60°C drying oven for 1 hour before taking it out. Repeat the above steps 2 to 3 times to ensure that the hydrogel is fully and evenly coated on the carrier surface.
[0072] (1) Preparation of gel carrier without adding Fe ions
[0073] Powdered chitosan was placed in a 10% acetic acid solution and fully dissolved at 80°C to prepare a chitosan solution, in which the mass fraction of chitosan was 3%. A 2% mass fraction glutaraldehyde solution was added to the chitosan gel for cross-linking modification to obtain an amino-rich cationic gel. The mass ratio of chitosan solution to glutaraldehyde solution was 250:1, and stirred for 1-2 hours. Add a foaming agent, a polyether polyol and a catalyst to the mold according to mass. The mass fractions of each component were 6 parts of a foaming agent, 70 parts of a polyether polyol and 1.5 parts of a catalyst. During the stirring process, aromatic diisocyanates were gradually added, in which 7 parts of isocyanates were added. At this time, uniform and fine bubbles will gradually form inside the system. Nitrogen was filled into the polyurethane soft foam in a sealed mesh device, and the pressure was controlled at 0.05 MPa~0.08 MPa to control the foam size. The inflated polyurethane carrier was dissolved in an N,N-dimethylformamide solution to dissolve the polyurethane film in the pores to ensure that a pore size of about 0.3mm~0.4mm was formed on the carrier surface. The foaming agent is a mixture of triethylamine and dichloromethane, and the mass ratio of the two is 1:1. The polyether polyol is selected from one or more of polyether 330, polyether 330N, polyether 320, polyether 230, polyether 220, etc. The catalyst is dibutyltin dilaurate. Isocyanate is selected from one or more of toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, and naphthalene-1,5-diisocyanate. When the foam is uniformly matured under low temperature conditions, the temperature is controlled between 30°C and 40°C. Oxygen is filled into the prepared gel to generate bubbles inside the gel. When uniform and fine bubbles are formed inside the gel, the prepared large-pore carrier is immersed in the gel for 5 minutes, and the carrier is taken out and placed in a 60°C drying oven for drying for 1 hour before being taken out. Repeat the above steps 2 to 3 times to ensure that the hydrogel is fully and evenly coated on the carrier surface.
[0074] (2) Preparation of the control group
[0075] Add a foaming agent, polyether polyol and catalyst to the mold according to the mass. The mass fraction of each component is 6 parts of foaming agent, 70 parts of polyether polyol and 1.5 parts of catalyst. During the stirring process, aromatic diisocyanate is gradually added, wherein 7 parts of isocyanate. At this time, uniform and fine bubbles will gradually form inside the system. Nitrogen is filled into the polyurethane soft foam placed in a sealed mesh device, and the pressure is controlled at 0.05 MPa~0.08 MPa to control the foam size. The inflated polyurethane carrier is dissolved in the polyurethane film in the pores using N,N-dimethylformamide solution to ensure that the carrier surface forms a pore size of about 0.3mm~0.4mm. The foaming agent is a mixture of triethylamine and dichloromethane, and the mass ratio of the two is 1:1. The polyether polyol is selected from one or more of polyether 330, polyether 330N, polyether 320, polyether 230, polyether 220, etc. The catalyst is dibutyltin dilaurate. The isocyanate is selected from one or more of toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, and naphthalene-1,5-diisocyanate. When the foam is uniformly matured under low temperature conditions, the temperature is controlled between 30°C and 40°C.
[0076] Prepare three 250mL conical flasks, add activated sludge of the same concentration and three groups of different carriers, 10 each. The carrier without gel was used as the control group, the carrier with only gel was used as experimental group 1, and the carrier with amino-rich Fe ion gel was used as experimental group 2. At a temperature of 25±2℃, the beaker was stirred at a speed of about 300rpm using a shaker. The carrier in the beaker was taken out every 3 minutes, and the surface water was drained and weighed to detect the change of the activated sludge mass adsorbed by the carrier over time. The results showed that the adsorption of activated sludge on the surface of the carrier without gel was 1.03 g / (g carrier), the adsorption of activated sludge on the surface of the carrier with only gel added reached 2.43 g / (g carrier), and the adsorption of activated sludge on the surface of the carrier with hydroxyl-rich iron-containing gel added reached 2.52 g / (g carrier). Compared with the carrier without gel added, the adsorption effect was increased by 1.49 g / (g carrier)
[0077] Example 4: Combination of nitrite carrier and anaerobic ammonium oxidizing bacteria carrier
[0078] The nitrite carrier and the anaerobic ammonia oxidation carrier are combined by gluing, wherein the large-pore carrier is used as the outer layer and the small-pore carrier is used as the inner layer. The adhesive is polyurethane glue, and the specific preparation method is as follows: 1 part of toluene diisocyanate is dissolved in 50 parts of N,N-dimethylformamide (DMF) and prepolymerized for 5 minutes. Then 1 part of polyethylene glycol is added to the solution. Then, at room temperature, sufficient mixing and stirring are carried out, and the whole reaction process lasts for 2 hours. Acetone of one-third of its volume is added to the polyurethane glue for dilution. One side of the AOB adsorption carrier is evenly coated with the diluted polyurethane glue, and then it is spread flat on the grid and left to stand for 5 minutes to ensure that the polyurethane glue no longer drips. After the polyurethane glue is slightly sticky, the AOB adsorption carrier is attached to the surface of the AnAOB adsorption carrier to ensure that the AnAOB carrier is completely wrapped. The entire carrier is placed in an oven at 60°C for drying. After drying, the carrier was taken out and placed in ultrapure water and cleaned using an ultrasonic device for 30 minutes to remove surface impurities and uncured adhesive.
[0079] (1) Preparation of gel carrier without adding cations and Fe ions
[0080] Add one third of the volume of acetone to the polyurethane glue for dilution. Evenly coat one side of the AOB adsorption carrier with the diluted polyurethane glue, then spread it flat on the grid and let it stand for 5 minutes to ensure that the polyurethane glue no longer drips. After the polyurethane glue becomes slightly sticky, place the AOB adsorption carrier close to the surface of the AnAOB adsorption carrier to ensure that the AnAOB carrier is completely wrapped. Place the entire carrier in an oven at 60°C for drying. After drying, take out the carrier and place it in ultrapure water, and use an ultrasonic device to clean it for 30 minutes to remove impurities and uncured adhesive on the surface.
[0081] (2) Preparation of the control group
[0082] Add one third of the volume of acetone to the polyurethane glue for dilution. Evenly coat one side of the AOB adsorption carrier with the diluted polyurethane glue, then spread it flat on the grid and let it stand for 5 minutes to ensure that the polyurethane glue no longer drips. After the polyurethane glue becomes slightly sticky, place the large-pore carrier that is not coated with gel tightly against the surface of the small-pore carrier that is not coated with gel to ensure that the small-pore carrier is completely wrapped. Place the entire carrier in an oven at 60°C for drying. After drying, take out the carrier and place it in ultrapure water, and use ultrasonic equipment to clean it for 30 minutes to remove impurities and uncured adhesive on the surface.
[0083] Prepare three 250mL conical flasks, add activated sludge of the same concentration and three different carriers in each group. The carrier without gel was used as the control group, the carrier with only gel was used as experimental group 1, and the carrier with amino-rich cation and Fe ion gel was used as experimental group 2. At a temperature of 25±2℃, the beaker was stirred at a speed of about 300rpm with a shaker. The carrier in the beaker was taken out every 3min, and the surface water was drained and weighed to detect the change of the activated sludge mass adsorbed by the carrier over time. The results showed that the adsorption amount of activated sludge on the surface of the carrier without gel was 1.46 g / (g carrier), the adsorption amount of activated sludge on the surface of the carrier with only gel added reached 3.05g / (g carrier), and the adsorption amount of activated sludge on the surface of the carrier with hydroxyl-rich iron-containing gel added reached 3.36 g / (g carrier). It can be seen that when the two carriers are combined, the adsorption amount of activated sludge is significantly improved.
Claims
1. A method for preparing a biological carrier suitable for the growth of nitrite bacteria and anaerobic ammonia oxidizing bacteria, characterized in that The steps include: Step 1: Preparation of amino-rich cationic gel The magnesium oxide particles are ground and then passed through a 150-mesh sieve; the powdered chitosan is placed in a 10% acetic acid solution and fully dissolved at 80° C. to prepare a chitosan solution; the magnesium oxide powder is added to the chitosan solution and stirred evenly, and then a 2% by mass glutaraldehyde solution is added for cross-linking modification to obtain an amino-rich cationic gel; Step 2: Preparation of a macroporous support that facilitates gas exchange Add a blowing agent, a stabilizer, a polyether polyol, triethanolamine and dimethylolbutyric acid into a reactor in a certain proportion, slowly add isocyanate thereto, stir at a speed of 600-900 rpm for 2-4 hours under the conditions of a vacuum degree of 0.10-0.12 MPa and a temperature of 25±2° C., and ripen to obtain a polyurethane soft foam; place the obtained polyurethane soft foam in a sealed reticulated device, fill it with nitrogen, and use an N,N-dimethylformamide solution to dissolve the polyurethane film in the pores to ensure that a pore size of 2 mm-4 mm is formed on the surface of the carrier; Step 3: Preparation of nitrosated carrier with positive potential and hydrophilic groups on the surface Fill the amino-rich cationic gel prepared in step 1 with oxygen to generate bubbles inside the gel. When uniform and fine bubbles are formed inside the gel, immerse the macroporous carrier prepared in step 2 in the gel for 5 minutes, take out the carrier and dry it; repeat the above steps 2 to 3 times to ensure that the gel is fully and evenly coated on the surface of the carrier; Step 4: Preparation of Amino-enriched Iron-containing Gel The iron oxide is ground and passed through a 150-mesh sieve; the powdered chitosan is placed in a 10% acetic acid solution and fully dissolved at 80° C. to prepare a chitosan solution; the iron oxide powder is added to the chitosan solution, and then a 2% by mass glutaraldehyde solution is added for cross-linking modification to obtain an amino-rich cationic gel; Step 5: Preparation of small pore size carriers for controlling dissolved oxygen permeation Add a blowing agent, polyether polyol and catalyst to the carrier mold, and gradually add aromatic diisocyanate during stirring, at which time uniform and fine bubbles will gradually form inside the system; place the obtained polyurethane soft foam in a sealed reticulated device, fill it with nitrogen, and use N,N-dimethylformamide solution to dissolve the polyurethane film in the pores to ensure that a pore size of 0.3mm~0.4mm is formed on the carrier surface; Step 6: Preparation of anaerobic ammonium oxidation carrier with iron ions and hydrophilic groups on the surface Fill the gel prepared in step 4 with hydrogen to generate bubbles inside the gel. When uniform and fine bubbles are formed inside the gel, immerse the small-pore carrier prepared in step 5 in the gel for 5 minutes, take out the carrier and dry it; repeat the above steps 2 to 3 times to ensure that the hydrogel is fully and evenly coated on the surface of the carrier; Step 7: Combination of nitrite carrier and anaerobic ammonium oxidizing bacteria carrier Using polyurethane glue as an adhesive, the nitrosation carrier prepared in step 3 and the anaerobic ammonium oxidation carrier prepared in step 6 are combined, wherein the nitrosation carrier prepared in step 3 is used as the top layer and the bottom layer, and the anaerobic ammonium oxidation carrier prepared in step 6 is used as the middle layer to form a sandwich structure.
2. The preparation method according to claim 1, characterized in that: In step 1, the mass fraction of chitosan in the chitosan solution is 2% to 4%; and the mass ratio of the chitosan solution to the glutaraldehyde solution is 250:
1.
3. The preparation method according to claim 1, characterized in that: In step 1, the content of magnesium oxide in the amino-rich cationic gel is 3%.
4. The preparation method according to claim 1, characterized in that: In step 2, the components are composed of 4 to 8 parts of foaming agent, 2 to 3 parts of stabilizer, 100 parts of polyether polyol, 6 parts of triethanolamine, 3 parts of dimethylolbutyric acid, and 1.14 parts of isocyanate in terms of mass fraction.
5. The preparation method according to claim 1, characterized in that: In step 2, the nitrogen inflation pressure is 0.10 MPa~0.11 MPa.
6. The preparation method according to claim 1, characterized in that: In step 4, the mass fraction of chitosan in the chitosan solution is 2% to 4%; and the mass ratio of the chitosan solution to the glutaraldehyde solution is 250:
1.
7. The preparation method according to claim 1, characterized in that: The mass fraction of iron oxide in the amino-rich cationic gel prepared in step 4 is 5%.
8. The preparation method according to claim 1, characterized in that: In step 5, the components are composed of 4 to 8 parts of blowing agent, 70 to 80 parts of polyether polyol, 0.5 to 1.5 parts of catalyst, and 7 to 8 parts of aromatic diisocyanate in parts by mass.
9. The preparation method according to claim 1, characterized in that: In step 5, after filling with nitrogen, the pressure is controlled at 0.05 MPa~0.08 MPa to control the size of the foam.
Citation Information
Patent Citations
Method for co-culturing nitrosation and anaerobic ammonia oxidation granular sludge by PVA gel beads
CN110498506A
Wastewater treatment devices, systems, and methods
WO2024118519A1